New Zealand Scholar Mamas: The Influence of Motherhood on Academic Careers - Hamilton, Samantha (Auckland University of Technology, 2017)
New Zealand women account for almost 64% of the academic workforce, (Statistics New Zealand, 2014), but are less represented in higher levels of Academia. This underrepresentation has been described and explained by various concepts such as the academic gender gap (Kalev, 2009), the chilly climate (Maranto & Griffin, 2011), and the leaky pipeline (Wolfinger, Mason, & Gouldren, 2009). There is currently a gap in research in New Zealand on the links between being a successful academic, being a mother, and the difficulties which arise from balancing these sometimes competing interests. This research utilised a subjective ontology, an interpretivist epistemology, a qualitative methodology and narrative methods to explore the stories of seven courageous academic women, namely ‘scholar mamas’. The purpose of this study is to explore the experiences of successful women academics around parenthood and to understand the impact on their academic careers over time. Research findings reveal five main themes: ‘manager and peer support’; ‘flexibility’; ‘career progression’; ‘approach to professional obligations and academic focus’; and ‘mummy logistics’. These themes are then grouped into three overarcing themes to shape the discussion: ‘The dominant maternity narrative’, ‘Shifting academic focus”, and ‘Heroes of the stories’ which represent the contributions this study has made to the area of academic careers, especially in the New Zealand context. ‘The dominant maternity narrative’ finding suggested that the participants in the study placed huge emphasis on the early stages of their journey, constructing a narrative that focuses on the positive and negative experiences while being pregnant, on parental leave and in the early stages of returning to work. The ‘Shifting academic focus’ finding suggested that the participants’ approach to both their career progression and how they met their professional obligations had changed since having their first child. Their career was no longer the priority and for some his even meant shifting to do just enough research to get by. The ‘Heroes of the stories’ finding suggested that participants place themselves as the centre of their stories. Beyond themselves, those who had positive experiences also tended to place significant emphasis on the role of their manager or Head of Department (HOD). The participants placed less emphasis on other support networks such as their partners, family and child-care facilities. The limitations of the study revolve around the criteria in which the participants were recruited. The participants were required to be at a particular point in their academic career and experiences and challenges which may have arisen from involving other women in the study may have been lost. The participants also engaged in unconscious ‘smoothing’ and downplayed some of the negative aspects of their experience, most notably in relation to their lack of career progression after having children. This smoothing could have also masked larger issues in regards to productivity and performance.
Keywords: Narrative Inquiry; Academia; Motherhood; Scholar Mamas